Totální pánevní exenterace - strategie a rozsah operačního výkonu - Šimša, J; Visokai, V; Lipská, L; Levý, M; Zachoval, R (Rozhledy v chirurgii, 2017)
INTRODUCTION: Pelvic exenteration is an essential part of complex treatment of advanced tumours of the small pelvis. The strategy of surgery is well known and consensual. However, the optimal extent of lymphadenectomy is still under discussion. The aim of this paper is to summarize the strategy of surgery and the extent of lymphadenectomy. METHODS: Review of the literature and retrospective analysis of 63 patients of our cohort, operated on at the Department of Surgery of the First Faculty of Medicine, Charles University and Thomayer Hospital between 1999-2015. CONCLUSION: The paper describes indications for pelvic exenteration, the strategy of surgery and the necessary extent of lymphadenectomy.
Keywords: lymfadenektomie; ženské pohlaví; exenterace pánve; Lymph Node Excision; retrospektivní studie; Humans; Female; nádory ženských pohlavních orgánů; Retrospective Studies; Pelvic Exenteration; kohortové studie; Genital Neoplasms, Female; lidé; Cohort Studies